Driving financial results is not the only priority! An exploration of the future role of chief financial officer: a grounded theory approach - Manoj Chatpibal; Wornchanok Chaiyasoonthorn; Singha Chaveesuk (Meditari Accountancy Research, 2023)
Purpose This study aims to develop a conceptual framework for the role of chief financial officer (CFO) in an ever-changing environment. As previous research focused on responding to specific crises, there have been theoretical and practical gaps in the role of CFO. The study's goal is to fill a critical gap by developing a comprehensive and integrated set of roles to assist the CFO in a constantly changing environment. Design/methodology/approach Using a grounded theory approach, semi-structured interviews and observations were conducted with 21 CFOs from various industries in Thailand, including foreign multinational corporations and domestic companies with international operations. CFOs were asked how they frame their roles in the face of an ever-changing environment and how they prepare for the future. Findings The iCFO model is developed, which identifies the critical “core” roles of the CFO in securing the business foundation, as well as the “future opportunities” roles that function as growth engines for long-term business strength. The research delves into the importance of integrity, ethical mindset and corporate governance in the role of the CFO. The iCFO model is designed to help guide future research and provide practical applications for CFOs in both domestic and international contexts. The term “core” refers to the CFO’s primary responsibilities, which include driving profitability, managing risks and optimizing business performance. The “future opportunities” component focuses on the roles that CFOs can play in strengthening the future of business by optimizing investment efficiency, driving digital transformation and being the CEO’s business partner. The findings also emphasized “integrity,” which must encompass all decisions, actions or recommendations made by the CFO. Originality/value The study offers unique perspectives on an emerging economy, providing new insights. Through interviews with 21 CFOs, it contributes empirical evidence on the development of roles in accounting and finance, emphasizing good governance practices. The findings highlight the integrated role of the CFO and their self-reflection on their value within the company. Significantly, the study's implications are relevant and applicable to a global audience, particularly in developing economies that prioritize growth. Future studies could incorporate integrated thinking into the iCFO model to address social, environmental and economic factors, making it more universally relevant. Additionally, exploring the adoption of the chief value officer context in developing markets could enable CFOs to expand their focus beyond financial metrics, embracing a comprehensive approach to value creation. By integrating these concepts into the iCFO model, CFOs can effectively drive sustainable and impactful business outcomes on a global scale.
Keywords: Risk Management in Financial Firms; Insurance and Financial Risk Management; Accounting and Organizational Management